The Mediating Role of Attitude: How Paid Communication and Source Credibility Influence the Intention to Recommend Digital Influencers - Yessa Jovita Sugiharto; Auditia Setiobudi (Almana : Jurnal Manajemen dan Bisnis, 2026)
The digital transformation in Indonesia has institutionalized influencer marketing as a core strategic tool, driven by the rapid growth of social media and increasing consumer reliance on influencer recommendations. Grounded in the Stimulus–Organism–Response (SOR) framework, this study examines the impact of paid communication (ad recognition), influencer credibility, and consumer attitudes on recommendation intentions within the digital landscape of Surabaya. This research aims at a deeper understanding of how sponsored content affects consumer behavior. Utilizing a quantitative approach, data from 160 purposively sampled followers of influencer Rachel Vennya were analyzed via Partial Least Squares–Structural Equation Modeling (PLS-SEM) 3.0. The empirical results demonstrate that influencer credibility is the most potent predictor of recommendation intention and a primary driver of positive consumer attitudes. Crucially, while ad recognition does not directly alter attitudes, it exerts a significant indirect influence on recommendation behavior through the mediating mechanism of perceived credibility. The study’s originality lies in establishing ad recognition as a critical antecedent that triggers behavioral responses through an integrated credibility-attitude pathway, offering strategic insights for managing influencer-brand partnerships in emerging digital markets. These findings suggest that brands should prioritize influencer authenticity and credibility over mere exposure in paid collaborations.